Pharmacological effects of a novel isosorbide-based butyrylcholinesterase inhibitor - RYDER, SHEILA (My University, 2008)
Isosorbide-2-benzylcarbamate-5-benzoate, a novel butyrylcholinesterase inhibitor, shows interspecies variation in its inhibitory activity (IC50 of 4.3 nM for human plasma butyrylcholinesterase, but 1.09 ?M for mouse plasma butyrylcholinesterase). Stability studies revealed that this drug is resistant to hydrolysis by human plasma (no degradation in 1 h). However, it was found to undergo rapid degradation when incubated with mouse plasma or mouse liver homogenate, yielding benzyl carbamate and benzoic acid. The addition of the carboxylesterase inhibitor bis-(4-nitrophenyl) phosphate (BNPP) inhibited the degradation of the novel drug, indicating that it may be a substrate for both butyrylcholinesterase and carboxylesterase. The absence of carboxylesterase from human plasma explains the drug's stability in this medium. In vivo, pharmacodynamic studies on single doses of 1 mg/kg to naive male C57BL/6 mice revealed maximal plasma butyrylcholinesterase inhibition 20 min after intraperitoneal administration (~60% inhibition) and 1 h after administration by gavage (~45% inhibition). While this plasma butyrylcholinesterase inhibition was short-lived, the drug also penetrated the blood?brain barrier resulting in a slight (10?15%) but persistent (?72 h) reduction in brain butyrylcholinesterase activity.
PUBLISHED
PMID: 18606399
Keywords: Butyrylcholinesterase; Inhibition; Carboxylesterase; Hydrolysis; Butyrylcholinesterase; Cholinesterase inhibitors; Hydrolysis; Inhibition; Stability; Neuroscience